THE INTERNAL CONFLICT OF MUSLIMS AND THE URGENCY OF THE MAINSTREAM OF MULTICULTURAL ISLAMIC EDUCATION IN FORMING ISLAMIC UNITY (Case Study of the Shia-Sunni Conflict in Sampang Madura) - Muhammad Asrori; Maskuri Maskuri (Universitas Islam Malang, 2022)
After the death of the Prophet Muhammad, the burden of history was borne by Muslims for disputes that started from political issues. The successor to the leadership of the Prophet became the first problem and even became a prolonged problem. Starting from this political dispute, later it will spread to other issues, such as issues of theology and ideology, including the Shia-Sunni intersection which is also a continuation of political problems in the early phase of Islam. Meanwhile, multicultural Islamic education initiated by several Muslim scientists often only discusses the relationship between Islam and other religions. In fact, the problem of internal disputes among Muslims is equally important to be resolved. This study uses qualitative research methods with the type of case study research. The results of the study show the urgency of multicultural education in an effort to re-tighten (taqri@b) Muslims by adhering to the values of multicultural Islamic education. The values of Islamic education include ta'aruf (knowing each other), ta'awun (helping each other), tasamuh (tolerant), tawasuth (moderate), tawazun (harmony), al-'adl (justice) and zuhud.Keywords:Ã‚Â Multicultural Islamic Education, ukhuwah Islamiyah, Shia, Sunni.